Effects of waterlogging on microbial activity, soil nutrient availability, nutrient uptake, and yield of tolerant and sensitive onion genotypes - Pawar, Amol R.; Patil, Sushant Sukumar; Patil, Mayur B.; Mahadule, Payal A.; Gade, Komal Anil; Arunachalam, Thangasamy; Mahajan, Vijay B. (Frontiers in Plant Science, 2025)
IntroductionRainfall variability during the monsoon season poses a major challenge to onion production, especially due to waterlogging stress in clay loam soils. Saturated conditions reduce soil aeration, disrupt microbial activity and nutrient transformations, and impair nutrient uptake and crop performance.MethodsTo investigate these effects, a field experiment was conducted under a split-plot design with flatbed layout to assess changes in soil physical properties, microbial activity, nutrient availability, and their combined effects on nutrient uptake and bulb yield in eight onion genotypes (two tolerant and six sensitive).Results and DiscussionWaterlogging increased bulk density by 5.30% and reduced infiltration rate by 76.5% compared to control. At 50 days after transplanting (DAT), microbial biomass carbon declined by 67.6%, while dehydrogenase, urease, acid phosphatase, and alkaline phosphatase activities declined by 55.8%, 33.9%, 33.9%, and 10.2%, respectively. Available macronutrients (N, P, K, S, Ca, Mg) and micronutrients (Fe, Cu, Mn, B) were significantly reduced at 55 DAT compared to 45 DAT. These changes led to reduced nutrient uptake and yield across genotypes. However, tolerant genotypes Accession 1666 and Bhima Dark Red (BDR) Selection exhibited better tolerance, with only 21.7% and 18.1% yield reductions, compared to 41.6–64.8% in sensitive types. Raised bed planting further improved performance of tolerant genotypes under waterlogged conditions.ConclusionThese findings highlight genotypic selection and raised-bed cultivation as effective strategies to mitigate waterlogging stress in monsoonal onion systems.